Cover Picture: Ligand Noninnocence in Coinage Metal Corroles: A Silver Knife‐Edge (Chem. Eur. J. 47/2015). Issue 47 (16th November 2015) - Thomas, Kolle E.; Vazquez‐Lima, Hugo; Fang, Yuanyuan; Song, Yang; Gagnon, Kevin J.; Beavers, Christine M.; Kadish, Karl M.; Ghosh, Abhik
Abstract : In contrast to noninnocent copper corroles and essentially innocent gold corroles, silver corroles appear to be poised on a knife‐edge between the two electronic‐structural descriptions. The summit trail of Mount Sir Alexander, a peak of the Canadian Rockies described by mountaineer Chris Goulet as a knife‐edge that only a mouse can walk on, provides an apt metaphor for silver corroles. For more details see the Full Paper by K. M. Kadish, A. Ghosh et al. onpage 16839 ff.